PENGARUH PROGRAM ECOBRICK TERHADAP BUDAYA BERSIH DI KELAS 3 SDN 1 BABAKANMULYA - Ridwan Suwandi; Irfan Fajrul Falah (STKIP Subang, 2025)
This study was motivated by the low level of students’ environmental awareness and the lack of understanding of plastic waste management in elementary schools. The purpose of this research was to determine the effect of the Ecobrick program on improving the cleanliness culture of third-grade students at SDN 1 Babakanmulya. This study employed a quantitative approach with a pre-experimental design, specifically the One Group Pretest–Posttest Design. Data were collected through questionnaires and documentation administered before and after the implementation of the Ecobrick program. The data were analyzed using a paired sample t-test to identify differences between the pretest and posttest results. The findings showed a significant increase in students’ cleanliness culture after participating in the Ecobrick program, as indicated by the value of t = 2.135 and a significance level of p < 0.05. These results demonstrate that the Ecobrick activity successfully enhanced students’ awareness of maintaining a clean environment, encouraged responsibility in managing waste, and fostered positive behavior toward environmental cleanliness in the school setting. In conclusion, the Ecobrick program proved to be an effective contextual learning medium that not only reduces plastic waste but also strengthens students’ environmental care character. The implication of this study emphasizes the importance of implementing sustainable school-based environmental programs to develop a culture of cleanliness from an early age.